Efficiency of Organic Binding of Trapped Iodide in Sporadic Goiter, Evaluated by the Decrease of Radioiodide Clearance - Harriet, Dige-Petersen (Nuklearmedizin - NuclearMedicine, 1977)
The decrease of early thyroid radioiodide clearance was determined in 33 patients with sporadic simple goiter, in 21 normal controls, in 38 hyperthyroid, and 9 hypothyroid patients. The clearance was measured between 5 and 30 min after injection of the tracer, 132I or 123 I, using a single detector system or a gamma camera, respectively. The decrease of clearance was given as the difference between the thyroid radioiodide clearance (ml blood/min) from 5–10 min and 25–30 min post injection.The relative decrease of clearance was similar in controls and in patients with simple goiter, indicating a normal binding efficiency of trapped iodide in the patients. The median 5–10 min clearance of controls was 85 ml blood/min, and of the patients 125 ml/min, the median decrease of clearance was 26 and 36 ml/min, respectively, i. e. about 30% in both groups; the higher early clearance values correlated significantly with the higher decreases. In the hyperthyroid patients the relative decrease was less pronounced, indicating that the increased iodide trapping in these patients was accompanied by a proportionately greater binding efficiency. In patients with primary hypothyroidism and elevated serum TSH levels the fractional binding of trapped iodide did not differ from normal.It was concluded that minor degrees of organic binding defects could not be demonstrated in patients with sporadic simple goiter.